Epidemiological study of emergency ambulance activation in the British Eastern Sovereign Base Area of Cyprus, September 2013 to August 2016. Issue 3 (23rd June 2019) - Jefferys, Sophie; Martin-Bates, A J; Harold, A; Withnall, R
Abstract : Objectives: To record the activation and use of the Eastern Sovereign Base Area (ESBA) emergency ambulance service of British Forces Cyprus between 1 September 2013 and 31 August 2016. To reflect on these findings in light of data from 1995 to 1998 to identify current treads and areas of development. Method: Retrospective epidemiological study of all activations of the ESBA emergency ambulance service within the study period. Results: 812 patients were treated over 3 years, an 80% increase in workload, of which 41% were entitled personnel. Forty-two per cent of activations were for medical complaints compared with 41% for trauma. The number of deaths remained static (n=15). Road traffic incidents (RTI) remain the top activation by type, but accounting for a smaller proportion of workload. RTI mortality has declined by 50%. Conclusion: The ESBA emergency ambulance service responded to double the activations, when compared with 18 years ago, with a significant shift to medical cases over trauma. This ESBA emergency ambulance provides a varied and vital service for the local community that also benefits Defence Medical Services personnel interested in the Pre-Hospital Emergency Medicine environment in order to maintain clinical skills and currency for the benefit of future deployments, both humanitarian and kinetic in nature.